Overload - Bulauitan, Joakim Miguel Manalang (Animo Repository, 2022)
Overload is a gym apparel brand aiming to improve the fitness lifestyles of gym goers. We do this through proper gym apparel attire specifically designed, studied, and measured to have the highest possible quality and superior fit for anyone who chooses to better their lives through fitness.